Peran Jabatan Notaris dalam Pelaksanaan Lelang Kepailitan - Chistopher Kendrick Adam; Rasji Rasji (UNES Law Review, 2023)
The issue in the case of the liquidation of PT. BPR Argawa Utama, the Deposit Insurance Corporation (LPS) revoked the business license as it was deemed unable to be restored. LPS has the authority to form a liquidation team, declare the bank's status as being under liquidation, and dissolve the legal entity of the bank. Issues arose regarding the execution of auctions by the Class II Auction Official, who lacks clear technical regulations. The authority of auction officials and the efforts of the liquidation team need further clarification through more detailed regulations or guidelines to ensure proper procedures and clear responsibilities in conducting auctions of assets from banks in liquidation. The presence of Class II Auction Officials in Indonesia is to enhance auction services and develop the auction official profession. Class II Auction Officials play a crucial role in ensuring legal certainty in auction execution. Auction reports have the same legal force as authentic deeds; therefore, Class II Auction Officials must prepare clear, readable, and complete auction reports. Additionally, Class II Auction Officials must read and explain the auction report to parties who do not understand. To ensure legal certainty, the role of Class II Auction Officials is vital in the execution of auctions.